Channel Impulse Response Length and Noise Variance Estimation for OFDM Systems with Adaptive Guard Interval - Gelle Guillaume; Kuchenbecker Hans-Peter; Kyamakya Kyandoghere; Haas Harald; Nguyen VanDuc (EURASIP Journal on Wireless Communications and Networking, 2007)
A new algorithm estimating channel impulse response (CIR) length and noise variance for orthogonal frequency-division multiplexing (OFDM) systems with adaptive guard interval (GI) length is proposed. To estimate the CIR length and the noise variance, the different statistical characteristics of the additive noise and the mobile radio channels are exploited. This difference is due to the fact that the variance of the channel coefficients depends on the position within the CIR, whereas the noise variance of each estimated channel tap is equal. Moreover, the channel can vary rapidly, but its length changes more slowly than its coefficients. An auxiliary function is established to distinguish these characteristics. The CIR length and the noise variance are estimated by varying the parameters of this function. The proposed method provides reliable information of the estimated CIR length and the noise variance even at signal-to-noise ratio (SNR) of 0 dB. This information can be applied to an OFDM system with adaptive GI length, where the length of the GI is adapted to the current length of the CIR. The length of the GI can therefore be optimized. Consequently, the spectral efficiency of the system is increased.